Style and Uzus Labels of Adjectives in the Russian Language Dictionaries: a Comparative Quantitative and Qualitative Study - Sharapat K. Mamirova; Gulzhana A. Kuzembayeva; Zhumagul A. Maydangalieva (RUDN Journal of Language Studies, Semiotics and Semantics)
The aim of the study is to examine the stylistic coloring of adjectives in Russian language dictionaries to establish similarities and differences in the use of vocabulary. The research material was eight dictionaries of the Russian language. The complex is a part of style and uzus in Russian language dictionaries, indicating historical, emotional-expressive and functional-stylistic adjectives, continuously modified and supplemented by new style and uzus terms, what is determined by the influence of social-historical processes, linguistic and extralinguistic factors on the development of the Russian language style. Analysis of the system of stylistic and uzus dubs in Russian language dictionaries shows a lack of uniformity in the marking of both individual adjectives and the class of adjectives as a whole, this makes it necessary to improve the normative description of adjectives in Russian and create a coherent system of markers for indicating the style and features of use of lexical unit.